Quantitative Analysis of the Factors that Impede Economic Development of The Egyptian Regions: A Proposed Vision for Regional Division and Population Redistribution - EL Ghawy, Hala (The Arab Journal of Administration, 2018)
The progress and economic growth levels that can be achieved depends to a large extent on the size of the available economic resources in the space of land and sources of mineral water and other riches of recoverable elements to take advantage of economic and capable of providing productive capacities. And whenever there is a diversity of available economic resources in the region whenever possible to achieve development rates stable to ensure the well-being and sustainability and the exploitation of human energies and it will not can only be done within the framework of providing incentives through tools that help to re-distribution of the population at the regional level and thus on the provincial level plan. Faced with Egypt a chance to be that the capture may occur once in human life of nations, where the population as much as possible working age population in the working age as little as possible, and then a low dependency ratio, this demographic situation will be an opportunity for developing countries in order to check mutations development has already benefited the Asian Tigers countries of this opportunity and the rehabilitation of the human forces to achieve greater economic progress. But standing in front of optimum utilization of the enormous manpower in Egypt obstacles which concerns us in this search overcrowding population of the governorates of Egypt on the Nile east and west bar, causing a waste of natural resources in the form of a decline in farmland and polluted down the course of the Nile. Based on the above comes the role of fiscal and monetary policy as one of the roles of active policies to redistribute the population within the framework of a regional economic development plan based on the support of economic projects from the perspective of sectors so that it is the work of an expanded investment maps for regions of Egypt change of form and space the current provinces of provinces constitute a point central tight on the course along the Nile to the large provinces of Egypt by accident up to the Red Sea to the east so that each port on the Red sea Governorate and the river port and back large desert connects them tape Railway and road. And determine the state priority projects for each region in the light of its potential to reflect the integrated and balanced between the regions and granting motivational advantages, including the instruments of fiscal and monetary policy to push the population to move to those areas which summoned to create the position higher than the Conservatives, a coordinator of the province, which is located on his shoulder coordination between the provincial task of the province both at the level of human resources or natural or financial and financing as well as this being a determinant of investment priorities within the framework of partnership with the relevant actors.